How the Portuguese footwear industry became a global leader: The role of technological innovation - Jayantilal, Shital (2019)
Portugal is a small economy on the south western tip of Europe. Its economy was thrown a huge blow with the global financial crisis of 2008. The country ended signing a 78 million euro bailout plan to help pull thorough yet the effects are still lingering. In this daunting context, Portuguese footwear industry has managed to transform itself gradually becoming an important player in the global arena and crucially important to the national economy. In this paper we aim to show that this accomplishment was possible due to the technological innovation introduced in this industry. We show that this introduction enabled to add value to the exports and, thus, launch the Portuguese footwear industry to worldwide spotlight. This industry of the Portuguese economy, shows the impact that technological innovation can have in terms of creating wealth, jobs and economic growth, even in the most dire of circumstances.